Tall Zirāʿa, Jordanien: Landwirtschaftlicher Komplex, ländliche Villa im orientalischen Stil oder Kloseranlage? Die Ausgrabungen im Areal III - Kenkel, Frauke; Rothe, Ursula (e-Forschungsberichte des DAI, 2023)
The excavation in May 2014 on Tall Zirāʿa focused on area III in the southern part of the tall plateau. Excavations in this area in Summer 2008 had revealed a large Byzantine building complex with a courtyard with mosaic floor, a barrel-vaulted cistern and an oil mill. The main purpose of the spring season 2014 was to dig test trenches to gain further information about the complex, like its extension or function. Within these works an ancient Greek inscription on a round mosaic, already discovered in 2008 but covered with soil for its protection, could be revealed.